The combination of T-2 toxin and acrylamide synergistically induces hepatotoxicity and nephrotoxicity via the activation of oxidative stress and the mitochondrial pathway. (15th January 2021) - Hou, Lirui; Liu, Shuo; Zhao, Chong; Fan, Lihong; Hu, Hongbo; Yin, Shutao
Abstract: T-2 toxin is a common fungal toxin, which is not only widely found in wheat, barley, corn, and other food crops and their related products, but also in various animal feeds. Acrylamide (ACR) is mainly formed by the free amino acid, asparagine and reducing sugars, such as glucose and fructose, and is commonly found in potato chips, French fries, toast, coffee, and other foods. Therefore, people are highly likely to consume food via their daily diets that are contaminated with both T-2 toxin and ACR. Since liver and kidneys were possible toxic targets of both T-2 toxin and ACR, this study assessed whether combined exposure could increase hepatotoxicity and nephrotoxicity using both cell cultures and animal models. We used L02 and MARC-145 cells and treated with T-2 toxin (5–15 nM) and ACR (1–3 mM) alone or in combination with a fixed ratio of 1:200 (T-2 toxin/ACR). ACR (50 mg/kg, i.g., 5d) and T-2 toxin (5 mg/kg, i.g., 5d) were used to assess the biochemical, proteins and histplogical changes in C57BL/6N mice. Results showed the combination resulted in synergistic cytotoxicity in vitro, while significantly increasing liver and kidney toxicity in vivo. Mechanistically, T-2 toxin decreased Manganese superoxide dismutase expression, while ACR reduced catalase expression. These two mechanisms were converged in response to the combination, leading to enhanced oxidative stress generation. The findings highlighted the necessity to consider the combined toxicity during the safety assessment of these food-borne contaminants. Graphical abstract: Image 1 Highlights: The T-2 and ACR combination resulted in synergistic hepatocytotoxicity and nephrotoxicity in vitro. T-2 and ACR co-exposure led to enhanced liver and renal toxicity in vivo. The increased ROS and mitochondrial pathway activation contributed to the enhancement of hepatotoxicity and nephrotoxicity. It is necessary to consider the combined toxicity of T-2 and ACR during food safety assessments.